ANALYSIS OF RELATIONSHIP BETWEEN BRAND PERSONALITY AND CUSTOMER SATISFACTION ON A VEHICLE EXHAUST SOUND - Rhiu, Ilsun; Kwon, Sanghyun; Yun, Myung Hwan; Park, Dong Chul (International Journal of Industrial Engineering: Theory, Applications and Practice, 2016)
This study aims to understand the brand personality of vehicle exhaust sounds and how these elements affect the customer satisfaction in regards to exhaust sounds. Thus, a research model for exploring the relationship between brand personality and customer satisfaction was developed. This study was conducted on nine vehicles’ exhaust sounds which were engine acceleration sounds when the speed of the vehicle increased from 0 to 100km/h (zero to 100). The evaluation was conducted among 40 participants who each have a minimum of ten years’ driving experience and have no impairment in their hearing. The findings partly support the research model and confirm that brand personality dimensions are influencing factors in satisfaction for the vehicle exhaust sound. ‘Sophistication’ and ‘Confidence’ are more important for customer satisfaction of V6 and V8 cylinder exhaust sounds than the other brand personality scales. The research advances the understanding of the effect of brand personalities on customer satisfaction for vehicle exhaust sounds.